Poly-consultant patients: A symptom of the Chilean health care system? - Miranda Hiriart, Gonzalo; Saffie Gatica, Ximena (Acta Bioethica, 2014)
This paper shows a series of reflections resulting from an exploratory and qualitative study carried out in a Family Health Care Center of Santiago, Chile. The question guiding this paper consists in considering whether the high rate of poly-consultant patients is a symptom of malfunctioning of the public Chilean health care system. It is concluded that there is a discrepancy between patient demands and professional knowledge, evidencing lack of biomedical keys to interpret this type of demands. Given de absence of answers, these patients generally are derived to “psychosocial couples", without much clarity over the basis of this derivation; thus, accounting for some deficiencies of a health care system which pretends to operate under a “bio-psychosocial” paradigm. This is aggravated by the way the managing of health care is imposed in the last two decades, since these are patients which face the efficiency of institutions and they do not enter into the established goals assigned to the different diagnosis. Nevertheless, while the health care system seeks in a veiled way to get rid of these patients, these insist even more with their demands.